Development of Batik Pen Canting Tool using CNC Machine - Roslan, Muhammad Ezzad Firdaus; Mohid, Zazuli (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Batik is Malaysia artwork that has become hereditary culture from generation to generation. One of the problems faced by batik industry recently is increasing demand of batik products. Nowadays, overall processing time of batik from sketches to batik products may take around 2 to 3 days, where the batik process itself may take one full day to complete. On the other hand, the number of batik craftsmen is increasingly limited, many young people are less interested in becoming batik craftsmen. This paper describes how to development of a batik pen canting tool at CNC machine to increases production canting batik. The development is divided into several parts: design batik pen canting tool, three -axis CNC machine, temperature, wax and fabric. Next, the project is to design and create a Canting Batik Tool and integrate it with a CNC machine. Furthermore, this test is based on the observation of design batik pen canting tool, consistency of wax learning, temperature and the feed rate of the CNC machine in batik processing. Therefore, this research can be done to fulfil all the industries requirement in each product batik such as good surface finish, good accuracy and saving cost.